Determining of Cross Sections for 22Na (n,Î±) 19F reaction from Cross Sections of 19F(Î±,n) 22Na reaction using the reciprocity theory for the ground state - Youhana, H. M.; Sarsam, M, N.; Ebrahiem, S. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study, light elements 19F ,22Na for (Î±,n) and (n,Î±) reactions as well as Î±-particle energy from a threshold energy to 10 MeV are used according to the available data of reaction cross sections. The more recent cross sections data of (Î±,n) and (n,Î±) reactions are reproduced in fine steps 86.4 KeV for 22Na (n,Î±) 19F in the specified energy range, as well as cross section (Î±,n) values were derived from the published data of (n,Î±) as a function of Î±energy in the same fine energy steps by using the principle inverse reactions. This calculation involves only the ground state of 19F ,22Na in the reactions 19F (Î±,n) 22Na , 22Na (n,Î±) 19F.